Evaluation of calcaneal enthesophytes in insertional Achilles tendinopathy by radiography and magnetic resonance imaging: intra- and inter-observer reliability - Silveira Junior, Dario Maciel; Baumfeld, Tiago Soares; Baumfeld, Daniel Soares; Benevides, Wilel Almeida; Silva, Thiago Alexandre Alves (Journal of the Foot & Ankle, 2020)
Objective: Evaluate intra- and inter-observer variation in the presence of enthesophytes in patients with insertional Achilles tendinopathy on radiographic (X-ray) and magnetic resonance imaging (MRI) images. Methods: We selected X-ray and MRI images of 20 patients diagnosed with an injury. We sent a questionnaire to five foot and ankle surgeons and five radiologists. We obtained answers about diagnosis accuracy and the presence of insertional enthesophytes (bone spurs). Results: Intra-observer agreement with regards to diagnosis accuracy in the MRI analysis was a K of 0.77 (0.62 to 1.00), while in the X-ray analysis, the K was 0.95 (0.77 to 1.00). Intra-observer agreement on the presence of enthesophytes in the MRI analysis had a K coefficient of 0.90 (0.68 to 1.00) and intra-observer agreement in the X-ray of 0.93 (0.86 to 1.00). The evaluation of inter-observer agreement on the diagnosis accuracy had a K coefficient between 0.09 and 0.20. Inter-observer agreement regarding the presence of enthesophytes was a K value between 0.59 and 0.63 for the MRI and a K between 0.81 and 0.82 for the X-ray results. Conclusion: Intra-observer values for diagnosis accuracy of the MRI and X-ray tests indicated strong to almost perfect agreement, similar to the intra-observer values for evaluation of the presence of enthesophytes, but the X-ray had better agreement. In both tests, intra-observer agreement on the presence of osteophytes was weak in comparison to inter-observer agreement, yet in the inter observer evaluation of the presence of enthesophytes, the X-ray agreement was greater than the MRI values. Level of Evidence III; Diagnostic Study.